Sledgehamr: Simulating Scalar Fields with Adaptive Mesh Refinement - Malte Buschmann (The Astrophysical Journal)
Understanding the nonlinear dynamics of coupled scalar fields often necessitates simulations on a 3D mesh. These simulations can be computationally expensive if a large scale separation is involved. A common solution is adaptive mesh refinement, which, however, greatly increases a simulation's complexity. In this work, we present sledgehamr , an AMReX -based code package to make the simulation of coupled scalar fields on an adaptive mesh more accessible. Compatible with both GPU and CPU clusters, sledgehamr offers a flexible and customizable framework. While the code had been primarily developed to evolve axion string networks, this framework enables various other applications, such as the study of gravitational waves sourced by the dynamics of scalar fields.